Mechanisms Underlying Stage-1 TRPL Channel Translocation in Drosophila Photoreceptors. - Lieu, M.H.; Vallejos, M.J.; Michael, E.; Tsunoda, S. (PLoS ONE, 2012)
TRP channels function as key mediators of sensory transduction and other cellular signaling pathways. In Drosophila, TRP and TRPL are the light-activated channels in photoreceptors. While TRP is statically localized in the signaling compartment of the cell (the rhabdomere), TRPL localization is regulated by light. TRPL channels translocate out of the rhabdomere in two distinct stages, returning to the rhabdomere with dark-incubation. Translocation of TRPL channels regulates their availability, and thereby the gain of the signal. Little, however, is known about the mechanisms underlying this trafficking of TRPL channels.We first examine the involvement of de novo protein synthesis in TRPL translocation. We feed flies cycloheximide, verify inhibition of protein synthesis, and test for TRPL translocation in photoreceptors. We find that protein synthesis is not involved in either stage of TRPL translocation out of the rhabdomere, but that re-localization to the rhabdomere from stage-1, but not stage-2, depends on protein synthesis. We also characterize an ex vivo eye preparation that is amenable to biochemical and genetic manipulation. We use this preparation to examine mechanisms of stage-1 TRPL translocation. We find that stage-1 translocation is: induced with ATP depletion, unaltered with perturbation of the actin cytoskeleton or inhibition of endocytosis, and slowed with increased membrane sterol content.Our results indicate that translocation of TRPL out of the rhabdomere is likely due to protein transport, and not degradation/re-synthesis. Re-localization from each stage to the rhabdomere likely involves different strategies. Since TRPL channels can translocate to stage-1 in the absence of ATP, with no major requirement of the cytoskeleton, we suggest that stage-1 translocation involves simple diffusion through the apical membrane, which may be regulated by release of a light-dependent anchor in the rhabdomere.